The Bahamas : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2019)
The Bahamas appears to be resilient to current threats to its financial stability, but action is needed to safeguard against potential weaknesses. There is a large stock of problem assets that needs to be dealt with from a variety of perspectives: systemic risk monitoring, banking supervision, and crisis management. Vulnerabilities to natural disasters and external economic contagion heighten this need. The banking sector dominates the financial system and has focused on residential mortgages and consumer loans during a long period of economic stagnation. Despite poor growth the sector has remained profitable. However, the small domestic residential property market backing most secured lending is prone to shocks and illiquidity. This has historically led to high and persistent levels of nonperforming loans (NPLs), which significantly increase uncertainty and fragility in the banking system.